KUALITAS PELAYANAN DOKUMENTASI DAN INFORMASI PRODUK HUKUM PADA BAGIAN HUKUM SEKRETARIAT DAERAH KABUPATEN TOJO UNA-UNA - Gugule, Sri Hartini (Katalogis, 2017)
This research carried out with the purpose of knowing how the quality of employees to service documentation and product information on the law and the law of the laws secretariat Tojo Una-Una district. This research type is descriptive research. This study will provide an overview and explanation and interpret data in detail or with respect to the quality of employees on the laws and regulations. basic research using field research (field research) that is doing research in the field to obtain direct information and informants. techniques of data collection is done by observation techniques, interviews and documentation. while the informant is the head of the legal department, head of sub-section 2 (two) as providers of legal products and documentation, 1 (one) staff of the people, and the community as service users. Data analysis technique used is the interactive mode. data validity checking is done by triangulation of sources and methods.The results of this study indicate that the quality of service documentation and product information law at the law and the laws and the regional secretariat Tojo Una-una, by Parasuraman and Keller (2009: 52) can be seen from the aspects of physical facilities (Tangible), reliability (Realibity), responsiveness (Responsiveness), assurance (Assurance) and Empathy (Empaty).In business and efforts to improve service quality legal products, especially on the law and the laws and the regional secretariat Tojo Una-una.based on the results obtained can be concluded that the quality of service of employees of the documentation and information laws have been very good but there are some things that need to be improved so that the quality of employees to be better and more effectively.